Correlating Nanocrystalline Structure with Electronic Properties in 2D Platinum Diselenide. (21st June 2021) - Lukas, Sebastian; Hartwig, Oliver; Prechtl, Maximilian; Capraro, Giovanna; Bolten, Jens; Meledin, Alexander; Mayer, Joachim; Neumaier, Daniel; Kataria, Satender; Duesberg, Georg S.; Lemme, Max C.
Abstract: Platinum diselenide (PtSe2 ) is a 2D material with outstanding electronic and piezoresistive properties. The material can be grown at low temperatures in a scalable manner, which makes it extremely appealing for many potential electronics, photonics, and sensing applications. Here, the nanocrystalline structure of different PtSe2 thin films grown by thermally assisted conversion (TAC) is investigated and is correlated with their electronic and piezoresistive properties. Scanning transmission electron microscopy for structural analysis, X‐ray photoelectron spectroscopy (XPS) for chemical analysis, and Raman spectroscopy for phase identification are used. Electronic devices are fabricated using transferred PtSe2 films for electrical characterization and piezoresistive gauge factor measurements. The variations of crystallite size and their orientations are found to have a strong correlation with the electronic and piezoresistive properties of the films, especially the sheet resistivity and the effective charge carrier mobility. The findings may pave the way for tuning and optimizing the properties of TAC‐grown PtSe2 toward numerous applications. Abstract : An investigation of the nanocrystalline structure of different 2D platinum diselenide (PtSe2 ) thin films grown via thermally assisted conversion at low temperatures in a scalable manner is presented. The structural properties determined using scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, and Raman spectroscopy exhibit a strong correlation to the electronic and piezoresistive properties extracted from fabricated devices.